INTEGRATED MARKETING COMMUNICATION (IMC) SMK NUSAPERSADA TENGARAN DALAM MENJAGA EKSISTENSI DITENGAH PERSAINGAN SEKOLAH SWASTA - Angga Prastiyo (Bisnis-Net, 2023)
SMK Nusapersada Tengaran began operating in 2014 with pharmacy and multimedia majors. At the beginning of its operation, SMK Nusapersada Tengaran was able to open 3 classes, 2 classes majoring in pharmacy and 1 class majoring in multimedia. The establishment of new schools at the SMA / SMK / MA level, both public and private, has created competition in the world of education. Not only new schools but also old schools are competing to develop their quality and services so that they can attract the public. The purpose of the research is to further understand how the marketing strategy of SMK Nusapersada Tengaran can compete with other private schools and how SMK Nusapersada Tengaran approaches the audience with IMC (Integrated Marketing Communication) theory. The research type uses descriptive qualitative which refers to the case study research method with pattern matching technique. Several informants were interviewed, including the Principal of SMK Nusapersada Tengaran, the Head of PPDB (New Student Admission), students of SMK Nusapersada Tengaran, and prospective students of SMK Nusapersada Tengaran. Before conducting Integrated Marketing Communication (IMC) SMK Nusapersada Tengaran conducts planning using several such as Segmentation Targeting and positioning, Objective Setting and budgeting, The Communication Process and Consumer Behavior and uses IMC Tools such as Public Relations (PR), Personal Selling, Sales Promotion, Online / Social Media Marketing, Direct Marketing, Advertising.